Fecal microbial transplantation as a novel therapeutic for autism spectrum disorders: a review of the current literature - Gudka, Rebecca; Nyinoh, Iveren Winifred (Frontiers in Microbiomes, 2023)
Background: Autism spectrum disorders (ASD) are complex neurobiological conditions with poor long-term outcomes and limited treatment options. The microbiota-gut-brain axis proposes a pathway by which the gut microbiota links to ASD. Fecal microbial transplantation (FMT), whereby the gut microbiota is replaced with that of a healthy individual, shows promise for the treatment of neurobiological conditions. This review examines the current evidence for the use of FMT as a therapeutic for ASD. Discussion: ASD and associated gastrointestinal symptoms are improved with FMT, potentially due to the engraftment of features of a healthy gut. Longer treatment regimens which include daily maintenance doses appear to be the most effective long-term therapeutic option, with benefits persisting 2-years post-intervention. Evidence is mixed regarding the use of preparatory treatment. Considering the sex-bias in ASD research, small sample sizes and lack of placebo-control arms, randomized-controlled trials would be of benefit to the evidence base regarding the use of FMT as a therapeutic option for ASD. Conclusion: FMT is a promising new therapeutic for ASD, but the evidence base is in its infancy.